USING BAMBOO DANCING METHOD TO IMPROVE READING SKILL - Fitri Novia (Universitas Islam Ogan Komering Ilir Kayuagung, 2017)
The aim of this study was to prove whether or not there was a significant difference in students’ reading skill between students who were taught using bamboo dancing and that of those were not. A quasi-experimental method was applied. The sample of this study was the tenth grade of SMA N 4 Kayuagung which consisted 62 students. The purposive sampling method was used to select the sample. A written test was used in the form of multiple choice to collect the data. Content validity and IDIF was used to find out the validity. Kuder Richardson (KR-21) was used to measure the reliability. A t-test was used to analyze the data. Based on the result of independent sample t-test, the value of t-obtained was 13.631 at significance level p<0.05 in two-tailed testing and df=60, the critical value of t-table was 2.0003. Since the value of t-obtained (13.631) was higher than t-table (2.0003) and p-value (0.000) was less than α value 0.05, the null hypothesis (H0) was rejected and alternative hypotheses (Ha) was accepted. It meant that there was a significant difference in students’ reading skill between students who were taught using bamboo dancing and that of those who were not. In short, a bamboo dancing method could improve students’ reading skill